The vegetation of Yura (Arequipa, Peru) - Galán de Mera, Antonio; Laboratorio de Botánica, Facultad de Farmacia, Universidad San Pablo-CEU (2023)
In this paper we describe the vegetation of Yura and its surroundings using the Braun-Blanquetphytosociological method. As a result, we report 3 new associations (Equiseto gigantei-Escallonietumangustifoliae, Pohlio longicollis-Rhodoscirpetum yurensis and Atriplici myriophyllae-Mesembryanthemetumcrystallini) and 3 new alliances (Muehlenbeckio fruticulosae-Helogynion stramineae, Polypogonointerrupti-Pohlion longicollis and Atriplici myriophyllae-Mesembryanthemion crystallini) of base-richsaline environments. In addition, Lycio distichi-Helogynetum stramineae is presented as a correctedname and the area of the Schino mollis-Prosopidetum calderensis association is extended to the NW. Insum, nine plant communities have been observed, among which the Pohlio longicollis-Rhodoscirpetumyurensis association is worth highlighting, as it presents a recently described Cyperaceae, associatedwith a bryophyte possibly recorded for the first time in southern Peru at a much lower altitude thanknown.